Intracranial electrophysiological recordings on a swine model of mesial temporal lobe epilepsy - Zhu, Fengjun; Wang, Hanwen; Li, Lin; Bragin, Anatol; Cao, Dezhi; Cheng, Yuan (Frontiers in Neurology, 2023)
Objective: To test the feasibility and reliability of intracranial electrophysiological recordings in an acute status epilepticus model on laboratory swine. Method: Intrahippocampal injection of kainic acid (KA) was performed on 17 male Bama pigs (Sus scrofa domestica) weighing between 25–35 kg. Two intracranial electrodes were implanted bilaterally along the sensorimotor cortex to the hippocampus. Brain electrical activity was recorded 2 hours daily for 9–28 d. Three KA dosages were tested to evaluate the quantities capable of evoking status epilepticus. Local field potentials (LFPs) and multi-unit discharges (MUDs) were recorded and compared before and after the KA injection. The epileptic patterns including high-frequency oscillations (HFOs) were quantified up to 4 weeks after the KA injection. Results: The KA dosage test suggested that a 10 µL (1.0 μg/μl) intrahippocampal injection could successfully evoke status epilepticus lasting from 4 to 12 h. At this dosage, eight pigs (50% of total) had prolonged epileptic events in the later 4 weeks of the video-SEEG recording period. Four pigs (25% of total) had no epileptic activities, and another four (25%) had lost the cap or did not complete the experiments. Animals that showed epileptiform events were grouped as E+ (n=8) and the animals showing no signs of epileptic events were grouped as E- (n=4). A total of 46 electrophysiological seizures were captured in the 4-week post-KA period from 4 E+ animals. A significant increase of hippocampal HFOs rate (num/min) was observed in the E+ group, however the E- showed no change or a decrease contrarily. The between-group comparison showed much higher HFO rates in E+ vs. E- (F = 35, P < 0.01). Significance: This study measured intracranial electrophysiological activity in a swine model of KA-induced mesial temporal lobe epilepsy. Using the clinical intracranial electrodes, we distinguished abnormal EEG patterns in the swine brain. The high test-retest reliability of HFO rates in the post-KA period suggests the utility of this model for studying mechanisms of epileptogenesis. The use of swine may provide satisfactory translational value for clinical epilepsy research.